Sorghum genotypes for cereal bar production - Queiroz, Valéria Aparecida Vieira; Carneiro, Heliete Lopes; Deliza, Rosires; Rodrigues, José Avelino Santos; Vasconcellos, José Heitor; Tardin, Flávio Dessaune; Queiroz, Luciano Rodrigues (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to develop a cereal bar with pop sorghum and evaluate it for consumer acceptance, as well as to identify sorghum genotypes and processing methods for pop sorghum production, in order to obtain a higher yield. Processing methods without (STH) and with hydrothermal treatment (CTH) of grains before expansion were evaluated. The CTH treatment reduced the percentage of nonexpanded grains in about 36% and increased pop sorghum yield in about 80%. In the STH process, the genotypes BRS 310, BR 501, BR 506 and CMSXS 283 yielded the lowest percentage of nonexpanded grains and the greatest pop sorghum expansion capacity. In the CTH, 'BRS 310' and 'CMSXS 283' genotypes showed the best performance. A survey on acceptance and the purchasing intention was performed in Londrina, PR, and in Rio de Janeiro, RJ, Brazil. It was found that the cereal bar with pop sorghum was accepted by 98.4 and 76.5% of consumers, and the average scores, in a 1‑9 scale, was 7.7 for Londrina and 7.1 for Rio de Janeiro. As for the purchasing intention, 88.8% of Londrina’s testers and 80.6% of "Cariocas" attributed above‑4 scores ("maybe do not buy, maybe buy") on the 7‑point scale used.